A Regulation-Based Security Evaluation Method for Data Link in Wireless Sensor Network - Claudio S. Malavenda; F. Menichelli; M. Olivieri (Journal of Computer Networks and Communications)
This article presents a novel approach to the analysis of wireless sensor networks (WSN) security, based on the regulations intended for wireless communication devices. Starting from the analysis and classification of attacks, countermeasures, and available protocols, we present the current state on secure communication stacks for embedded systems. The regulation analysis is based on civil EN 50150 and MIL STD-188-220, both applicable to WSN communications. Afterwards, starting from a list of known WSN attacks, we use a correspondence table to match WSN attacks with countermeasures required by regulations. This approach allows us to produce a precise security evaluation and classification methodology for WSN protocols. The results show that current protocols do not present a complete coverage of security issues. While this conclusion is already known for many WSN protocols, to the best of our knowledge this is the first time a complete methodology is proposed to base this assertion. Moreover, by using the proposed methodology, we are able to precisely identify the exposed threats for each WSN protocol under analysis.